Building a large-scale distributed object system for a multilingual programming environment - Muckelbauer, P.A.; Russo, V.F. (Advances in Parallel and Distributed Systems, IEEE Workshop (APADS '93, 1993)
Object-oriented programming techniques are increasingly gaining attention as a solution to some of the software engineering problems plaguing the construction of large software projects. Unfortunately, object-oriented interfaces are usually only enforced and usable through language mechanisms, making it impossible for components in a large-scale distributed environment to interact. The authors are investigating the possibility of creating a runtime notion of an object's interface and allowing to that interface. The project also provides a mechanism to dynamically generate local references (proxies) to objects in different address spaces (domains) so that once this conformance is confirmed, operations can be invoked on the object in a mechanism compatible with the client's programming language. This mechanism gives us seemingly local, native references to remote objects within a language.